2015
DOI: 10.1007/s12170-015-0463-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Gene Expression of Inflammatory Markers in Human Peripheral Blood Cells: A Systematic Review

Abstract: Regular physical activity seems to be one of the most important contributors to prevent disease and promote health. Being physically active reduces the risk of developing chronic diseases such as cardiovascular disease, diabetes, and some types of cancers. The molecular mechanisms are however not fully elucidated. Depending on duration and intensity, exercise will cause disruption of muscle fibers triggering a temporary inflammatory response. This response may not only involve the muscle tissue, but also perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 74 publications
4
93
0
3
Order By: Relevance
“…While the molecular mechanisms involved are not yet fully understood, strong evidence supports the importance of increased shear stress, as a result of exercise-induced increased heart rate and blood flow, as the primary signal acting on the endothelium produced by exercise [118], resulting in down-regulated endothelial angiotensin II type 1 receptor expression, leading to decreases in NADPH oxidase activity and superoxide anion production, which in turn decreases ROS generation, and preserves endothelial NO bioavailability and its protective anti-atherogenic effects [119]. Of further note, atherosclerosis is a chronic inflammatory disease [120] and several studies support an inverse correlation between physical exercise and serum markers of inflammation such as Creactive protein (CRP), tumor necrosis factor-α (TNFα) and Interleukin-6 [121123,124. In addition, recent meta analysis of 28 individual studies showed that physical exercise has several non-acute effects expected to reduce atherogenesis; i.e., decreasing adhesion molecule VCAM-1 and ICAM-1 expression, reducing the angiogenic factor VEGF, and increasing endothelial progenitor cells (EPC) [125].…”
Section: Physical Exercisementioning
confidence: 99%
“…While the molecular mechanisms involved are not yet fully understood, strong evidence supports the importance of increased shear stress, as a result of exercise-induced increased heart rate and blood flow, as the primary signal acting on the endothelium produced by exercise [118], resulting in down-regulated endothelial angiotensin II type 1 receptor expression, leading to decreases in NADPH oxidase activity and superoxide anion production, which in turn decreases ROS generation, and preserves endothelial NO bioavailability and its protective anti-atherogenic effects [119]. Of further note, atherosclerosis is a chronic inflammatory disease [120] and several studies support an inverse correlation between physical exercise and serum markers of inflammation such as Creactive protein (CRP), tumor necrosis factor-α (TNFα) and Interleukin-6 [121123,124. In addition, recent meta analysis of 28 individual studies showed that physical exercise has several non-acute effects expected to reduce atherogenesis; i.e., decreasing adhesion molecule VCAM-1 and ICAM-1 expression, reducing the angiogenic factor VEGF, and increasing endothelial progenitor cells (EPC) [125].…”
Section: Physical Exercisementioning
confidence: 99%
“…On the other hand, epidemiological data show that regular moderate physical activity contributes to the prevention of disease and promotion of health (63, 64). Recently, in a systematic review based on studies examining PBMC gene expression, it has been demonstrated that prolonged and regular physical activity promotes inflammation dampening effects, possibly resulting in a reduced risk for the development or exacerbation of CIDs (66). …”
Section: Common Pathways In Cidsmentioning
confidence: 99%
“…Cancer-protective mechanisms of physical activity have mainly focused on alterations in levels of sex hormones, inflammatory markers, and growth factors (14)(15)(16). It is plausible that such changes are due to physical activity-induced transcriptional changes, as physical activity has been shown to induce widespread transcriptional effects (17)(18)(19)(20). This may be of particular relevance for BRCA1 mutation carriers given that their cancer predisposition is likely the result of haploinsufficiency associated with heterozygosity, thereby increasing genomic instability and accelerating the mutation rate of other critical genes (including the second copy of BRCA1; ref.…”
Section: Introductionmentioning
confidence: 99%